Technology of processing CT data of the Knee Joint - Sedlák, Josef; Charvát, Ondřej; Madaj, Martin (Manufacturing Technology Journal, 2010)
Aloarthroplastic is the basic surgery method in orthopaedics, which handles the insult to the normal human joint function [1]. Achieving of advance in development of knee replacements is possible only on the basis of complex and deep knowledge of those problems and on experimental judgment of physical properties of used materials including successful implantation before introduction into the practice. In orthopaedics, technology of 3D models creation and theirs application is at the beginning and there is an effort to decide what effective manner has to be used for total benefit from the viewpoint of patient medication. This long-term task can be verified only in practice.
Keywords: Knee Joint; Reverse Engineering; CAD software; Rapid Prototyping; CT data